2016
DOI: 10.18535/jmscr/v4i11.109
|View full text |Cite
|
Sign up to set email alerts
|

Assessment for Risk Factors of Non-communicable Diseases in Employees (Teaching and Non-Teaching) Working in Medical College, Maharashtra

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
2
1
Order By: Relevance
“…5 Our study showed hypercholesterolemia in 12.68%, hypertriglycerides in 25.35%, raised LDL in 2.82%, raised VLDL in 15.49% and low HDL in 22.82% which were much lower than the other studies done by Sharma et al, Alzeidan et al and Akintunde et al 1,5,7 The prevalence of cigarette smoking was in 8.45% among males and none of the women smoke which was similar to Sabale et al was (6.2%) and Ketkar et al and was much lower than Takur et al was (24.3%), Sharma et al was (12.8%) and Alzeidan et al was (12%). [5][6][7][8]11 The habit of alcohol consumption was seen in 7.04% which was lower than Sabale et al was (13.04%) as this study included all staff and higher than Sharma et al was (2.6%) as the study included only the habit of heavy drinking.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…5 Our study showed hypercholesterolemia in 12.68%, hypertriglycerides in 25.35%, raised LDL in 2.82%, raised VLDL in 15.49% and low HDL in 22.82% which were much lower than the other studies done by Sharma et al, Alzeidan et al and Akintunde et al 1,5,7 The prevalence of cigarette smoking was in 8.45% among males and none of the women smoke which was similar to Sabale et al was (6.2%) and Ketkar et al and was much lower than Takur et al was (24.3%), Sharma et al was (12.8%) and Alzeidan et al was (12%). [5][6][7][8]11 The habit of alcohol consumption was seen in 7.04% which was lower than Sabale et al was (13.04%) as this study included all staff and higher than Sharma et al was (2.6%) as the study included only the habit of heavy drinking.…”
Section: Discussioncontrasting
confidence: 54%
“…10 Study by Sabale et al showed a mean waist circumference of 91.3 cms in males and 92.4 cms in females, obesity in 56% and abdominal obesity of 55.5% in males and 63.5% in females. 6 Study by Akintunde et al showed that generalized obesity of 38.3%. 1 The substantially high prevalence of overweight, obesity and central obesity as per India specific guidelines may be owing to the sedentary life-style and desk job of administrative employees who formed a major portion of the study population.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation